Green Cost Management pada Desa Wisata: Kajian Akuntansi Manajemen Lingkungan (Lembaga Pengembangan Kinerja Dosen, 2025)
The sustainable management of tourism villages requires not only promotional strategies but also cost planning and control that consider environmental aspects. This is crucial given the increasing pressure on natural resources and local socio-cultural values. This study aims to examine the implementation of Green Cost Management (GCM) in ecotourism-based tourism village projects, focusing on four main variables: green cost planning, environmental cost control, environmental performance, and the sustainability of tourism village projects. This research employs a qualitative approach using a case study method. The research site was purposively selected in Senaru Village, Bayan District, North Lombok Regency. The population consists of tourism village stakeholders, and purposive sampling was used to select seven key respondents: the Village Head, Village Treasurer, Chairperson of the Tourism Awareness Group (Pokdarwis), Homestay Operator, Traditional Leader, Representative from the Environmental Agency, and an Academic. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The results indicate that the implementation of GCM is not yet systematically integrated; environmental cost planning and control are not specific, environmental performance lacks standardized indicators, and the sustainability of the tourism village is not yet supported by long-term environmentally-based planning. The implications of this study highlight the importance of strengthening the capacity of village officials, preparing environmental planning documents, and providing technical assistance from academics and related institutions to support the implementation of GCM in advancing sustainable tourism village development.